HUKUM INVESTASI DITINJAU DARI THE PRINCIPLE OF SOVEREIGN EQUALITY - erlina erlina; Zulherman Idris; Radian Suparba (UIR Press, 2023)
The results of the WTO panel's decision were recorded in the DS 592 lawsuit. The final panel report was issued on October 17, 2022, stating that the export policy and the obligation to process and refine nickel minerals in Indonesia proved to violate WTO Article XI provisions. GATT 1994 and cannot be justified by Article XI.2 (a) and XX (d) GATT 1994. The purpose of the provisions of WTO Article XI.1 GATT 1994 states that each WTO member country is prohibited from making restrictions other than tariffs, taxes and other duties , and not other restrictions including quotas and licensing of imports or sales in the framework of export. There are two consequences that will be faced by Indonesia, including having to pay losses to the European Union (EU) as the plaintiff arising from the nickel export ban. Second, facing retaliation from the European Union's ban on other Indonesian commodities or in fiscal prohibition instruments. Problems in the field of capital loading are related to demands and threats to the principle of equality of sovereignty against investors who are treated differently, amid demands to make as much profit as possible. The principle can be a way out for investors to withdraw from investing in arbitration or court courts, so that Indonesia will suffer losses. Thus, it is necessary to explain the concept to understand the principle of sovereign equality and its influence in Indonesian laws and regulations in the field of capital protection, so as to provide a clear picture of the treatment of investors.